Studying the effects of Exposure to Chemicals on The brain and Nervous System and The risk of Chemical Pollution - Dr. Nagham Mahmood Aljamali*1; Dr.Shireen Ridha Rasool; Dr.Ali Jassim Al-Zuhairi; Dr. Saher Mahmood Jwad; Dr.Rajaa Abdulameer Ghafil (International Journal of Brain Sciences, 2026)
Scientific research and studies on chemical pollution show that exposure of the brain and nervous system to chemicals causes serious damage ranging from cognitive, motor, and nerve cell disorders to chronic diseases such as Alzheimer's and neurological paralysis. These substances (such as lead ions, mercury, solvents that combine and dissolve easily in the blood, and pesticides) disrupt neurotransmitters and cause cell damage, especially during the early stages of body development. This necessitates a thorough study of the risks of chemical pollution to protect neurological health. The effects of neurotoxicity generally manifest as a range of adverse symptoms affecting the brain, depending on the nature of the chemical, the dosage, the duration of exposure, and the age, physiology, and immunity of the individual exposed. The severity of the observed effects increases with increasing dose. Exposure to a small or low dose of a neurotoxic chemical may lead to subjective symptoms such as headache, dizziness, blurred vision, and elevated blood pressure, but these effects are usually reversible. With increasing doses, neurological changes may occur, eventually leading to irreversible morphological alterations. The degree of abnormality required to indicate neurotoxicity of a chemical agent is a matter of debate, as prolonged exposure may result in loss of consciousness, memory loss, anemia, severe immunodeficiency, acute seizures, and other adverse effects. Heavy metal challenging is appreciated as an investigative device for recognizing experience of poisonous metals in the body and improving to oversee probable health consequences correlated with this revealing and its impressions on the nervous technique.
Keywords: Heavy metals; brain; chemical pollution; nervous cells; neurotoxicity